The Reality of Physics Teachers' Use of Formative Assessment Tools in Dhofar Governorate from the Perspective of senior Teachers and Educational Supervisors (Journal Of Educational and Psychological Researches, 2026)
This research aims to explore the reality of physics teachers’ use of formative assessment tools in Dhofar Governorate from the perspectives of senior teachers and educational supervisors. It also sought to identify differences in the mean scores of participants’ responses regarding the extent of use, based on the variables of job role and gender. To achieve these objectives, the descriptive-analytical method was employed, as it is most suitable for describing phenomena without delving into causal relationships. A questionnaire was developed, consisting of six main domains with 24 items. The research was applied to a sample of 53 participants, including 22 educational supervisors and 31 senior teachers affiliated with the schools of Salalah. According to the statistics obtained from the Department of Statistics and Information at the Directorate General of Education in Dhofar for the academic year 2023–2024. The results revealed that the average of senior teachers regarding the use of formative assessment tools was 3.67, indicating a high level of use, while the average of educational supervisors was 2.98, indicating a moderate level. Oral questioning emerged as the most frequently used formative assessment tool, followed by written questions and homework assignments, whereas project-based assessment was the least used. The findings also indicated significant differences regarding participants’ responses based on job role. There are no significant differences based on gender. The research recommended training teachers in the effective use of formative assessment tools and raising their awareness of the importance and advantages of written assessment tools in evaluating students’ understanding, as they are more effective than oral questioning.